Analysis of equations arising in gyrotron theory - Cepıtis, Janis; Dumbrajs, Olgerts; Kalis, Harijs; Reinfelds, Andrejs; Strautins, Uldis (Nonlinear Analysis: Modelling and Control, 2012)
The gyrotron is a microwave source whose operation is based on the stimulated cyclotron radiation of electrons oscillating in a static magnetic field. Powerful gyrotrons can be used to heat nuclear fusion plasma. In addition, they have found a wide utility in plasma diagnostics, plasma chemistry, radars, extra-high-resolution spectroscopy, high-temperature processing of materials, medicine, etc. However, the main application of gyrotrons is in electron cyclotron resonance heating in tokamaks and stellarators. Equations describing gyrotron operation are ordinary differential equations and Schrödinger type partial differential equations. The present paper provides a survey of the analytical and numerical results concerning these equations obtained by our group in the last decade.